Optimizing Helical Tomotherapy for Left-Sided Breast Cancer: A Retrospective Dosimetric Study of a Novel Virtual Organ-Arc Block - Yingtao Fang MS; Wenliang Yu MS; Jian Qiao PhD; Yanju Yang MS; Jing Mi MS; Lei Yu PhD; Ying Guo MS; Jiazhou Wang PhD; Weigang Hu PhD (Technology in Cancer Research & Treatment)
Introduction Left-sided breast cancer radiotherapy requires precise dose modulation to balance target coverage and organ-at-risk (OAR) sparing. This study evaluates a novel Organ and Arc-based Directional Block (OABD Block) in helical tomotherapy planning to address this challenge. Methods In this single-institutional retrospective study, 10 post-mastectomy patients with left-sided breast cancer receiving adjuvant radiotherapy were studied. Target volumes included chest wall, internal mammary, axillary, and supraclavicular lymph nodes, with a dose of 50 Gy over 25 fractions. Using a tomotherapy planning system, an OABD Block was configured to incorporate arc structures and protect organs-at-risk. For each patient, helical tomotherapy plans were prepared with and without the OABD Block, keeping field width, pitch, and modulation factors identical. Additionally, static intensity-modulated radiotherapy (IMRT) plans were created on a United Imaging system. Treatment plans were evaluated by dose-volume parameters, conformity and homogeneity indices, and mean doses to targets and normal tissues. Results Helical tomotherapy with the OABD Block provided a mean conformity Index of 0.79 for the Planning Target Volume, higher than plans without the block (0.73) but below IMRT plans (0.88). The homogeneity Index averaged 0.14 with the block, 0.18 without, and 0.11 in IMRT. For the internal mammary lymph node region, D95% reached 5007.7 cGy with the block, compared to 5001.1 cGy without and 4897.9 cGy in IMRT. The OABD Block reduced the mean heart dose to 478.7 cGy, compared to 533.5 cGy without and 638.9 cGy in IMRT. Left lung V5 was 48.0% with the block, 52.7% without, and 53.2% in IMRT; V20 was also lowest with the block (17.5%) versus without (20.3%) and IMRT (24.3%). Conclusion Adding the OABD Block to helical tomotherapy improved internal mammary lymph node dose coverage and reduced exposure to organs at risk.